Making architecture : the Getty Center - Williams, Harold M.; Williams, Harold Marvin.;Huxtable, Harold.;Roundtre, Richard (Los Angeles, California : J. Paul Getty Trust, 1997)
This publication marks the completion of a fourteen-year project plan, design, build and occupy the Getty Center. The design of the structures and the character of the programs inhabiting them would develop concurrently was a singular feature of this architectural undertaking.
Introduction/ Harold M. Williams -- Project chronology -- The clash of symbols/ Ada Louise Huxtable -- A concert of wills/ Stephen D. Rountree -- A vision for permanence/ Richard Meier -- Site diagrams, models, and plans -- Construction -- The Getty Center, Spring, 1997 -- Project credits.
Keywords: ART CENTERTS -- DESIGNS AND PLANS